2022
DOI: 10.3389/fpsyg.2021.802408
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Social Support in the Relationship Between Parenting Styles and Adolescent Drug Abuse Identification

Abstract: Adolescent drug abuse is a social issue of global concern, causing a serious burden of diseases for individuals, families and society. To design effective prevention and intervention strategies for adolescent drug abusers, the predictive factors associated with drug abuse must be quantified and assessed. This study explores the similarities and differences between the parenting styles of adolescent drug abusers and non-drug abusers and applies a structural equation model to analyze the mechanisms involved betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…We did not find school engagement to be a significant predictor of class membership. While previous literature has found that negative school engagement is significantly associated with service use in community mental health settings, 27 to our knowledge, no studies have explored school engagement as a predictor of school mental health service use or need. Still, it is critical for schools and CSMBHS professionals to ensure that students have positive school engagement, as research consistently links positive school engagement and school connectedness with lower mental health needs 43,44 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We did not find school engagement to be a significant predictor of class membership. While previous literature has found that negative school engagement is significantly associated with service use in community mental health settings, 27 to our knowledge, no studies have explored school engagement as a predictor of school mental health service use or need. Still, it is critical for schools and CSMBHS professionals to ensure that students have positive school engagement, as research consistently links positive school engagement and school connectedness with lower mental health needs 43,44 .…”
Section: Discussionmentioning
confidence: 81%
“…School engagement measured experiences with peers and adults in school using five items based on previous research. 27 Students responded to each question about their experiences in the last 12 months on a 4-point Likert scale: (1) how often did you feel that the school work you were assigned to do was meaningful and important, (2) overall feeling about going to school; (3) how interesting they thought most of their courses at school had been; (4) how important they thought that the things they had learned were going to be in later life; (5) how often their teachers at school let them known when they were doing a good job with school work. We summed them and create a total score ranging from 0 to 15, with higher scores meaning higher levels of positive school engagement (α = .774).…”
Section: Variablesmentioning
confidence: 99%
“…However, the use of behavioral control and effective monitoring of children"s behaviour as linked to less involvement in problem behaviour including substance abuse and Juvenile delinquency Steinberg, Fletcher & Darling, 1994;Zhu & Shek, 2021). The findings of this study on drug abuse, parenting styles and social support identified parenting styles as the significant predictors of adolescent substance abuse identification, and it further indicated that imperfect parenting behaviors/styles are a risk factor for the development of substance abuse (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 66%
“…Many studies have confirmed that there is a significant relationship between social support and relapse tendency or a significant negative correlation, which is consistent with the results of this study (Caravaca-Sánchez & García-Jarillo, 2020; Massah et al, 2016; Rodríguez-Sáez et al, 2021). Some studies have used different social support scales and come to the same conclusion, such as a significant negative correlation between family support and relapse tendency (Li Liu et al, 2022; Xia et al, 2022; Zeng & Tan, 2021). In addition, this study found that exercise self-efficacy and QoL were significantly negatively correlated with relapse tendency, indicating that exercise self-efficacy acquired with social support (such as training guidance and obtaining positive comments) and QoL (physical and mental health) play an essential role in promoting health and reducing the tendency of relapse among those with substance use disorders.…”
Section: Discussionmentioning
confidence: 93%